Degree and Complexity of Non-conscious Emotional Information Processing – A Review of Masked Priming Studies - Rohr, Michaela; Wentura, Dirk (Frontiers in Human Neuroscience, 2021)
Whether and to what degree information can be processed non-consciously has been a matter of debate since the emergence of psychology as a science. Emotional information, in particular, has often been assumed to have a privileged status because of its relevance for well-being and survival (e.g., to detect a threat). Indeed, many studies have explored non-conscious processing of evaluative (i.e., “emotional” in a broad sense) or emotional (e.g., facial expressions) features using the “silver bullet” of non-consciousness research – the masked sequential priming paradigm. In its prototypical form, this paradigm involves the categorization of target stimuli according to valence (e.g., is the target positive or negative?). Each target is preceded by a briefly presented prime that is followed by a mask to constrain awareness. Non-conscious processing is inferred from subtle influences of the prime on target processing, that is, whether responses are faster if prime and target are valence-congruent or not. We will review this research with a focus on three questions: First, which methods are used in this area to establish non-conscious processing? Second, is there evidence for non-conscious extraction of evaluative information? Third, is there evidence for non-conscious processing beyond a simple valence (positive/negative) discrimination, for example, processing of emotion-specific information? We will highlight important current debates and potential directions in which the field will move in the future.